2012
DOI: 10.1165/rcmb.2011-0433oc
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Injury and Altered Lung Function after Ozone Inhalation in Mice with Chronic Lung Inflammation

Abstract: Surfactant protein-D (Sftpd) is a pulmonary collectin important in down-regulating macrophage inflammatory responses. In these experiments, we analyzed the effects of chronic macrophage inflammation attributable to loss of Sftpd on the persistence of ozoneinduced injury, macrophage activation, and altered functioning in the lung. Wild-type (Sftpd 1/1 ) and Sftpd 2/2 mice (aged 8 wk) were exposed to air or ozone (0.8 parts per million, 3 h). Bronchoalveolar lavage (BAL) fluid and tissue were collected 72 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 45 publications
6
44
0
Order By: Relevance
“…Moreover, macrophage inflammation increases with age in these mice, findings consistent with an important regulatory role of Sftpd in innate immunity (48). In previous studies we showed that low-level pulmonary inflammation accompanying loss of Sftpd in young mice is correlated with prolonged injury, oxidative stress, and altered pulmonary mechanics in response to inhaled ozone (18). The effects of chronic and progressive inflammation and the development of emphysema, which mimics biological responses in humans (6), on the response to inhaled ozone are unknown and were investigated in aging Sftpd Ϫ/Ϫ mice.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, macrophage inflammation increases with age in these mice, findings consistent with an important regulatory role of Sftpd in innate immunity (48). In previous studies we showed that low-level pulmonary inflammation accompanying loss of Sftpd in young mice is correlated with prolonged injury, oxidative stress, and altered pulmonary mechanics in response to inhaled ozone (18). The effects of chronic and progressive inflammation and the development of emphysema, which mimics biological responses in humans (6), on the response to inhaled ozone are unknown and were investigated in aging Sftpd Ϫ/Ϫ mice.…”
supporting
confidence: 80%
“…A DAB Peroxidase Substrate Kit (Vector Labs) was used to visualize binding. The number of positively staining macrophages and type 2 cells was quantified microscopically for each slide, as previously described (18). Each enumerated cell was assigned a staining intensity score on a scale of 0 -4 with 0 ϭ no staining, 1 ϭ light staining, 2 ϭ medium staining, 3 ϭ dark staining.…”
Section: Animals and Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was collected for protein and lipid analysis. The cell pellet was re-suspended in 1mL buffered saline for cytology and RT-PCR (Atochina-Vasserman et al, 2009; Casey et al, 2005; Groves et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The primary mechanism of clearance, at the alveolar surface, is via the activity of the alveolar macrophages (Forman et al, 1980(Forman et al, , 1982Hartmann et al, 1984;Stringer et al, 1995;Bates and Fisher, 1996;Kaul and Forman, 1996;Yagisawa et al, 1996;Tang et al, 2001;Iles et al, 2002;Jimenez et al, 2002;Quintero and Wright, 2002;Tao and Kobzik, 2002;Chin et al, 2003;Hjort et al, 2003;Laskin et al, 2003;Fakhrzadeh et al, 2004a,b;Rao et al, 2004;Kanj et al, 2005Kanj et al, , 2006Rothen-Rutishauser et al, 2005;Hu et al, 2006Hu et al, , 2007Sunil et al, 2007;Baker et al, 2008;Gaschler et al, 2008;Geiser et al, 2008;Manzer et al, 2008;Naito et al, 2008;Yamasaki et al, 2008;Jordan et al, 2009;Kuronuma et al, 2009;Pauluhn, 2009;Ryman-Rasmussen et al, 2009;Woodruff et al, 2009;Hoogerwerf et al, 2010;Snyder et al, 2010;Fuchimoto et al, 2011;Hristova et al, 2011;Poole et al, 2011;Groves et al, 2012;…”
Section: Inflammation In the Lungmentioning
confidence: 99%